The Influence of Inflation, Interest Rates, and Exchange Rates on Stock Prices of Consumer Goods Sector Companies Listed on the Indonesia Stock Exchange During 2020–2024 - Natalia Putri Simamora; Dhinvel Harzialby; Marista Halimah Saragih; Ribka Sari Butar– Butar; Dita Eka Pratiwa (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study examines how inflation, interest rates, and exchange rates affect the stock prices of consumer goods companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. This research is important because macroeconomic factors can have a significant impact on stock price fluctuations, especially in the consumer goods industry, which is relatively stable but still vulnerable to economic changes. This study uses a descriptive-associative research design with a quantitative approach. Secondary data were obtained from the official websites of Statistics Indonesia, Bank Indonesia, and the Indonesia Stock Exchange (IDX). The data used in this study are time series data covering five years. The sample consists of five companies selected using a purposive sampling technique. The data were analyzed using multiple linear regression with SPSS software. The analysis includes classical assumption tests, t-test, F-test, and coefficient of determination. The results show that inflation, interest rates, and exchange rates have a positive and significant effect on stock prices. Simultaneously, these three variables also have a significant effect on stock prices. The adjusted R-Square value is 0.187, which means that inflation, interest rates, and exchange rates explain 18.7% of the variation in stock prices, while the remaining percentage is influenced by other factors outside this study.